MEMAHAMI YOHANES 14:1-14 DENGAN TINJAUAN EKSEGETIS SOSIAL-SAINTIFIK - Nurliani Siregar; Sukanto Limbong; Dominggus Pote; Hasahatan Hutahaean (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2021)
This study aims to understand John 14:1-14 by using the social-scientific exegetical method. The research prioritizes a historical review and explanation of historical writings on the Way and the Truth and Life from the Old Testament (OT) to New Testament (NT) times. Jesus is the way, the truth, and the life in the face of today's postmodern relativism. The results of the study conclude that